Epidemiologic study of multiple sclerosis - Mahmood Abedidni; Reza Habibi Saravi; Ashraf Zarvani; Manssor Farahmand (Journal of Mazandaran University of Medical Sciences, 2008)
(Received 12 Jan, 2008 ; Accepted 10 Sep, 2008) AbstractBackground and purpose: Despite edidemiologic similarity of multiple sclerosis worldwide, prevalence shows considerable variability. According to Kurtzke, Iran is considered to have a low prevalence. In this study, we wanted to estimate the prevalence period and Indicate Epidemiologic aspect of MS in Mazandaran Province, North of Iran.Materials and methods: A cross- sectional Registered case Study Conducted in 2007 on all definite MS Patients that live and reside within Mazandaran, as well az being a member of the Mazandaran MS Society. 582 difinite patients (161 men and 421 woman) were identified. The patients were Viu interview and questionaire to record demographic and Case related information. According to the national Sensius Reports, the population of Mazandaran was 2,893,087.Results: The mean (SD) age of the participants was 34.3 (9.4) years. The MS period pervalence was 20.1 per 100,000{95% confidence interval(CI) 18.7-22.1}. The Female/male ration was 2.6 and MS rates were highest among 3rd decade. Visual and sensory distorbancec were thw most common initial persontations with prevalence of 40.1 %( 95% CI: 38.5-42.9 ) and 34.2% ( 95% CI: 32.8 – 36.1), respictively.Conclusion: Mazandaran is in medium MS prevalence area. This is in clear contrast with background hypothesis, but other epidemiologic indices were almost pursuant with pervious information. J Mazand Univ Med Sci 2008; 18(66):82-86(Persian)